If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8.5(x+6)+1=2.4x-12
We move all terms to the left:
8.5(x+6)+1-(2.4x-12)=0
We multiply parentheses
8.5x-(2.4x-12)+51+1=0
We get rid of parentheses
8.5x-2.4x+12+51+1=0
We add all the numbers together, and all the variables
6.1x+64=0
We move all terms containing x to the left, all other terms to the right
6.1x=-64
x=-64/6.1
x=-10+1/2.0333333333333
| 0.25x1.50=x | | -5-6b=-5b+2 | | 4x+5(7x-3)=9(3x-9) | | n+6.5=4.7 | | 3(3b+2)=-20 | | 4/6=5/6+y | | 18.1-x=0.7 | | 8x-28+8x22=90 | | 7/(x-2)=7/11 | | 180=3x+2x+x | | x+52=520 | | 4x+7=-2x+2 | | 130=3x+2 | | 6-3=4x+1 | | 6(x-3)=-2x+2 | | 6u+8-9u=-12 | | .60p+.20(40-p)=0 | | 8(4–x)+x=8+x | | 3(1+7x)=-165 | | v/7=-5 | | -7=6.7+x | | 5.4x-2.3=40.9 | | 2x=5x–2 | | 0.75y-2=y-17 | | 14-2=-2(10-x) | | .04(x=3)-2=0.4x | | 2x+3x=192 | | -49b=44.1 | | 2(2-3x)+5(2x-3)=20-5x | | 0.75-2=y-17 | | -w+135=205 | | -6(3x-8)=-6 |